2011
DOI: 10.4049/jimmunol.1003470
|View full text |Cite
|
Sign up to set email alerts
|

A Meningococcal Factor H Binding Protein Mutant That Eliminates Factor H Binding Enhances Protective Antibody Responses to Vaccination

Abstract: Certain pathogens recruit host complement inhibitors such as factor H (fH) to evade the immune system. Microbial complement inhibitor-binding molecules can be promising vaccine targets by eliciting antibodies that neutralize this microbial defense mechanism. One such antigen, meningococcal fH-binding protein (fHbp), was used in clinical trials before the protein was discovered to bind fH. The potential effect of fH binding on vaccine immunogenicity had not been assessed in experimental animals because fHbp bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
247
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(257 citation statements)
references
References 51 publications
8
247
1
1
Order By: Relevance
“…Binding of human FH decreases FHbp immunogenicity (24)(25)(26), and FHbp mutants with decreased binding of FH elicit higher protective antibody responses in human FH transgenic mice (16,24,27). Because R130 is an FH binding residue in variant group 1 proteins (28), we tested binding of human FH to the doublemutant FHbp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Binding of human FH decreases FHbp immunogenicity (24)(25)(26), and FHbp mutants with decreased binding of FH elicit higher protective antibody responses in human FH transgenic mice (16,24,27). Because R130 is an FH binding residue in variant group 1 proteins (28), we tested binding of human FH to the doublemutant FHbp.…”
Section: Resultsmentioning
confidence: 99%
“…FHbp mutants with decreased binding of human FH were shown to have enhanced immunogenicity in human FH transgenic mice (15,16,24,27). The stabilized double-mutant FHbp had approximately sevenfold lower affinity for human FH than the WT FHbp (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Since the formulation of Bexsero, subsequent research has suggested ways of producing more effective MenB vaccines, e.g., the use of fHbp modified so that it does not bind human factor H, 64,65 the removal of potential blocking antibodies, 66 or the use of engineered nOMVs with lower toxicity and overexpressing selected antigens. Thus the vaccine may be reformulated to improve protection provided.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that binding of fH to the fHBP in the vaccine might reduce the availability of epitopes during the immunization process. This was evaluated in a recent study by Beernink et al, who assessed the immunogenicity of fHBP-based vaccines in human fH transgenic mice that were immunized with fHBP or a mutant fHBP that eliminated fH binding (76). Though there was no statistically significant difference in SBA responses between the two vaccines, a logarithmic regression looked at the effect of the concentration of human factor H on immunogenicity and found that at high fH concentrations, the mutant vaccine generated slightly higher bactericidal responses.…”
Section: Evidence That Human Factor H Is the Ligand For Fhbpmentioning
confidence: 99%